Anais da V Jornada Científica da Faculdade Sul Fluminense- Resumos Simples - Barbosa, Marcus Vinicius; Triani, Fielipe da Silva (Revista Valore, 2020)
Anais da V Jornada Científica da Faculdade Sul Fluminense- Resumos Simples